2016
DOI: 10.4236/ajps.2016.715189
|View full text |Cite
|
Sign up to set email alerts
|

Heavy Metal Accumulation Potential of Some Wetland Plants Growing Naturally in the City of Kolkata, India

Abstract: Freshwaters are not only used locally in many developing countries but they are often over exploited for domestic purposes, agriculture and disposal of industrial wastes which result in an overload of excess nutrients, harmful chemicals and heavy metals. Plant species together with sediments and water samples collected from eleven aquatic water bodies in the vicinity of industrial units in Kolkata were studied for their potential to uptake Pb, Cd and Cr under field conditions. Cd and Cr concentrations in the s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
10
0
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 21 publications
(13 citation statements)
references
References 86 publications
1
10
0
2
Order By: Relevance
“…N. lotus, C. benghalensis, and P. stratiotes (TF>1) also exhibited considerable translocation potential for Ni (1.68), Cr (1.21) and Cr (2.50) respectively. This study corroborates the results of Jha et al (2016) who suggested that A. philoxeroides shows considerable promise not only as an efficient accumulator of Pb and Cd in its roots but its ability to rapidly uptake heavy metals even at very low ambient levels could also make it an efficient indicator of the aquatic ecosystem quality. Table 4: Bioaccumulation factor and Translocation factor * TF greater than 1, a BAF less than 10, h BAF greater than 10…”
Section: Mean Heavy Metals In Sediments and Soils Of Wetlandssupporting
confidence: 90%
See 4 more Smart Citations
“…N. lotus, C. benghalensis, and P. stratiotes (TF>1) also exhibited considerable translocation potential for Ni (1.68), Cr (1.21) and Cr (2.50) respectively. This study corroborates the results of Jha et al (2016) who suggested that A. philoxeroides shows considerable promise not only as an efficient accumulator of Pb and Cd in its roots but its ability to rapidly uptake heavy metals even at very low ambient levels could also make it an efficient indicator of the aquatic ecosystem quality. Table 4: Bioaccumulation factor and Translocation factor * TF greater than 1, a BAF less than 10, h BAF greater than 10…”
Section: Mean Heavy Metals In Sediments and Soils Of Wetlandssupporting
confidence: 90%
“…Pb level in the roots was highest in Eichonia crassipes (5.69 mg/kg) and least was in the roots of Ludwigia adscendens (0.15 mg/kg). All the plants harvested for this study were healthy and did not show any toxicity symptoms, however, excess Pb in plants had been reported to inhibit growth while Cd can inhibit photosynthesis and mineral assimilation causing leaf chlorosis, necrosis, and abscission (Adesuyi et al, 2015a;Jha et al, 2016). Ipomoea involucrata also had the highest level of Cd in its shoots (0.45 mg/kg) while the shoots of Phragmites australis, Eichonia crassipes, Ludwigia adscendens, and Phragmites australis all had the least Cd level (0.01 mg/kg) in their shoots.…”
Section: Mean Heavy Metals In Sediments and Soils Of Wetlandsmentioning
confidence: 96%
See 3 more Smart Citations